77.7k views
12 votes
If f ( x )=3 x2+4 x−2∧g ( x)=x2−2x+3 , Find an expression for ( f - g)(x)

User Papa John
by
5.0k points

1 Answer

9 votes

Answer:


(f-g)(x) = 2x^2+ 6x-5

Explanation:

Given


f(x) = 3x^2 + 4x - 2


g(x) = x^2 - 2x + 3

Required

Find
(f-g)(x)

In functions:


(f-g)(x) = f(x) - g(x)

Substitute values for f(x) and g(x)


(f-g)(x) = 3x^2 + 4x - 2 - (x^2 - 2x + 3)

Open bracket


(f-g)(x) = 3x^2 + 4x - 2 - x^2 + 2x - 3

Collect Like Terms


(f-g)(x) = 3x^2 - x^2+ 4x + 2x- 2 - 3


(f-g)(x) = 2x^2+ 6x-5

User Sakeena
by
5.0k points